Analysis of entropy generation in a power-law nanofluid flow over a stretchable rotatory porous disk. (December 2021) - Usman,; Ghaffari, Abuzar; Mustafa, Irfan; Muhammad, Taseer; Altaf, Yasir
Abstract: A theoretical entropy generation analysis is conducted by applying the MHD and nonlinear thermal radiation effects contained in porous material for a steady three-dimensional power-law nanoﬂuid flow near the stagnation point region. With the assistance of a thermally radiated non-uniform heat source /sink subject to convective boundary conditions, the heat transformation phenomenon is explored within the boundary layer over the stretchable rotatory disk. Multi-wall carbon nanotubes (MWCNTs) are incorporated in the ethylene glycol ( C 2 H 6 O 2 ) as a base fluid. The proposed problem of fluid flow is mathematically modeled. The governing nonlinear partial differential equations (PDEs) are lessened to highly mixed nonlinear ordinary differential equations (ODEs) after the utilization of appropriate transformations. The effects of several classes of relevant parameters upon total entropy generation and Bejan number profiles are investigated by numerically addressing the ODEs with the purpose of a well-known Keller Box method. Furthermore, the skin friction coefficients and local Nusselt number are calculated for shear-thinning and shear-thickening behaviors of the power-law fluid. Also, the total entropy generation increases for the Brinkman number and the permeability parameter but decreases for the material parameter, whereas the Bejan number has different behavior from entropy generation.